Proposta de metodologia para elaboração de carta de conflito de uso baseado em banco de dados geográfico como subsídio à gestão territorial aplicada no município de Poços de Caldas - MG - Mendonça, Misael de (Universidade Federal de São Carlos, 2005)
This work presents the research plan the methodology proposal for implementation of the Use Conflit Chart based on geographical database, as a subsidy to the territorial administration based on study of case of the Municipal district of Poços de Caldas MG. The application of the dynamic cartography, obtained through operations on maps the use of Geographic Information Systems, using attributes collected in order to represent all the municipal territorial extension, objectives to make possible the constant charts update with the new attributes implementation, supplying an up-to-date contribution for the territorial administration. The final Use Conflit Chart, obtained with the proposed described in this work, is a product of the procedures guided by a methodological flow data acquisition and operations using maps algebra techniques.
Keywords: Engenharia geológica; Sistemas de informação geográfica; Conflito de uso; Mapeamento geológico; Ágebra de mapas; ENGENHARIAS